2017
DOI: 10.1007/s11356-017-8666-5
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of the herbicide imazethapyr in mammalian cells by oxidative DNA damage evaluation using the Endo III and FPG alkaline comet assays

Abstract: We evaluated the role of oxidative stress in the genotoxic damage induced by imazethapyr (IMZT) and its formulation Pivot® in mammalian CHO-K1 cell line. Using the alkaline comet assay, we observed that a concentration of 0.1 μg/mL of IMZT or Pivot® was able to induce DNA damage by increasing the frequency of damaged nucleoids. To test whether the DNA lesions were caused by oxidative stress, the DNA repair enzymes endonuclease III (Endo III) and formamidopyrimidine-DNA glycosylase (Fpg), which convert base dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…For instance, it has been found to cause oxidative stress and endocrine disruption in rats (Yang et al 2018) and developmental toxicity associated to thyroid dysfunction in zebrafish (Li et al 2020). Finally, imazethapyr has also been reported by causing metabolic alterations in Cyprinus carpio (Moraes et al 2011), genotoxicity in tadpoles of Rhinella arenarum and Hypsiboas pulchellus species (Carvalho et al 2019;Perez-Iglesias et al 2017;Perez-Iglesias et al 2015), and also in mammalian cells (Soloneski et al 2017); however, the toxicity of herbicide is poorly characterized and needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been found to cause oxidative stress and endocrine disruption in rats (Yang et al 2018) and developmental toxicity associated to thyroid dysfunction in zebrafish (Li et al 2020). Finally, imazethapyr has also been reported by causing metabolic alterations in Cyprinus carpio (Moraes et al 2011), genotoxicity in tadpoles of Rhinella arenarum and Hypsiboas pulchellus species (Carvalho et al 2019;Perez-Iglesias et al 2017;Perez-Iglesias et al 2015), and also in mammalian cells (Soloneski et al 2017); however, the toxicity of herbicide is poorly characterized and needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…We could emphasize the importance of using the modified SCGE technique to assess oxidative damage introduced into the DNA of amphibians as a consequence of pesticide exposure. Our observations reveal that treatment with both Endo III and Fpg buffers induce an enhancement in the frequency of DNA damage duce lesions into cellular DNA, and thus increasing the length of the nucleoids (Collins and Azqueta, 2012;Demir et al, 2014;Soloneski et al, 2016Soloneski et al, , 2017. Furthermore, our results demonstrate that the modified SCGE assay using Fpg, but not Endo III, turned out to be highly sensitive and effective in detecting genetic oxidative damage introduced into the DNA of circulating blood cells of H. pulchellus tadpoles by the herbicide IMZT-based commercial formulation Pivot H ® at purine bases, but not pyrimidines.…”
Section: Discussionmentioning
confidence: 72%
“…Whereas IMZT did not induce chromosomal aberrations in rat bone marrow cells, both negative and positive results have been reported for CHO cells with and without metabolic activation, respectively (USEPA, j). Furthermore, several studies employing the conventional alkaline version of the comet assay have shown that IMZT is genotoxic to some nontarget organisms, i.e., bacteria Salmonella typhimurium and Escherichia coli (USEPA, 1989) and plants such as Allium cepa (Liman et al, 2015) as well as mammalian exposed in vitro cells (Soloneski et al, 2017). Recently, we demonstrated for the first time that the herbicide jeopardizes anuran amphibian Hypsiboas pulchellus tadpoles by inducing micronuclei induction and DNA primary damage evaluated the SCGE assay (Pérez-Iglesias et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Based on scientific evidence, it is fully justified to investigate the real, predicted, and perceived risks of pesticides endured by humans. Pesticides used at tobacco fields have been shown to increase DNA damage, as observed in cell lines [ 4 6 ], animal models [ 7 , 8 ], and human studies [ 9 11 ]. They were also already evaluated either as single chemicals [ 6 , 7 , 12 ] or as mixtures (reviewed by [ 13 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides used at tobacco fields have been shown to increase DNA damage, as observed in cell lines [ 4 6 ], animal models [ 7 , 8 ], and human studies [ 9 11 ]. They were also already evaluated either as single chemicals [ 6 , 7 , 12 ] or as mixtures (reviewed by [ 13 ]). The latter is the standard method of pesticide application in crop farming worldwide [ 13 ], including for Brazilian tobacco farmers [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%